The retrocondylar retinaculum (Osborne’s ligament) and Struther’s ligament - Martinez de Oliveira, Kennedy; Meggiolaro, Emilly Dutra Amaral; Oliveira , Maísa de Fátima Satiro; Gonçalves , Giuliano Roberto; Ramos , Lucas Nogueira; Veloso , Éwerton Machado; Grecco , Leandro Henrique; Almeida , Valério Landim de (Revista Peruana de Morfología, 2021)
Many of the musculofascial and osteofibrous structures of the upper limbs, and which are of the normal human structural constituent (pattern), are notably neglected in general anatomical descriptions. Their complex structures, and sometimes controversial or incomplete descriptions, have significant implications in important neurovascular conditions, such as compressive trauma, and those of orthopedic reconstructions. Thus, we objective a detailed study, structural and historical, of the literature, on two of the most important osteofibrous formations - the retrocondylar retinaculum (Osborne’s ligament), together with the aponeurosis of the flexor carpi ulnar muscle (Osborne’s fascia), and the Struther’s ligament in association with the supracondylar process and foramen homonym.